2023
DOI: 10.3389/fmicb.2023.1183018
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the Bovine Intramammary Bacteriome and Resistome from healthy cows of Swiss dairy farms in the Canton Tessin

Alicia Romanò,
Ivana Ivanovic,
Tina Segessemann
et al.

Abstract: Healthy, untreated cows of nine dairy herds from the Swiss Canton Tessin were analyzed three times within one year to identify the most abundant species of the intramammary bacteriome. Aseptically collected milk samples were cultured and bacteria identified using MALDI-TOF. Of 256 cows analyzed, 96% were bacteriologically positive and 80% of the 1,024 quarters were positive for at least one bacterial species. 84.5% of the quarters were healthy with somatic cell counts (SCC) < 200,000 cells/mL, whereas 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 100 publications
0
1
0
Order By: Relevance
“…Some phenotypically penicillin-susceptible staphylococci have the blaZ gene, but isolates negative for blaZ or mec rarely manifest resistance, indicating that genotypic AMR testing ( 176 ) may be good for the choice of antimicrobial drug for treatment. Another study from Switzerland to determine intramammary microbiome and resistome from the milk of healthy dairy cows reported a high prevalence of resistance to clindamycin and oxacillin (65 and 30%, respectively) in S. xylosus but not associated with chromosomal or plasmid-borne ARGs ( 177 ). The authors found that most resistance was justified by the presence of mobile genetic elements such as tetK -positive plasmids.…”
Section: Bovine Staphylococcal Mastitismentioning
confidence: 99%
“…Some phenotypically penicillin-susceptible staphylococci have the blaZ gene, but isolates negative for blaZ or mec rarely manifest resistance, indicating that genotypic AMR testing ( 176 ) may be good for the choice of antimicrobial drug for treatment. Another study from Switzerland to determine intramammary microbiome and resistome from the milk of healthy dairy cows reported a high prevalence of resistance to clindamycin and oxacillin (65 and 30%, respectively) in S. xylosus but not associated with chromosomal or plasmid-borne ARGs ( 177 ). The authors found that most resistance was justified by the presence of mobile genetic elements such as tetK -positive plasmids.…”
Section: Bovine Staphylococcal Mastitismentioning
confidence: 99%